An investigation of the prevalence and diversity of Anisakis in China: marine food safety implications - Zeng, Min-hao; Fang, Chuan-tao; Wang, Xiao-xu; Qadeer, Abdul; Qiu, Yang-yuan; Hong, Xiao-mei; Mahmoud, Mohamed H. (Frontiers in Microbiology, 2024)
Anisakis can cause Anisakiasis in humans if raw or undercooked fish is consumed. Symptoms of infection may include vomiting, acute abdominal symptoms, or allergies. In this study, we collected 187 commercially available marine fish from the Yellow Sea, East China Sea, and South China Sea. Among them, 79 were found positive containing 520 Anisakis worms. The average prevalence rate was found 42% in this investigation. Ninety-two worms from different sea areas were selected and analyzed for identification, revealing the presence of five different species, which are Anisakis pegreffii, Hysterothylacium aduncum, Hysterothylacium zhoushanense, Hysterothylacium amoyense, and Hysterothylacium sp. In the meta-analysis, three databases: PubMed, CNKI, and BaiduXueshu were searched for surveys on the prevalence of Anisakis in Chinese waters from January 2000 to December 2023. A total of 26 studies were included in this analysis of which 25 publications were retrieved from different databases and one being the present study. The pooled prevalence of Anisakis was 45% among commercially available marine fish. Variances in the prevalence of Anisakis were noted among the four seas, with the highest rates in the East China Sea and the Bohai Sea, reaching 53% [0.38; 0.68] and 49% [0.36; 0.62], respectively. The Prevalence of anisakis infection was significantly higher in astern parts such as Liaoning, Shanghai, and Zhejiang. Analysis of the host fish subgroups revealed that the orders of Anguilliformes, Scombriformes, and Gadiformes had high rates of infection. These findings suggest a significant prevalence of Anisakis, posing an increasing risk of infection for individuals. This study provides impactful information for implementing preventative measures against Anisakis.